2022
DOI: 10.1108/jima-06-2022-0177
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of key antecedents of religious brand attitude: a cross-cultural quantitative analysis using smart PLS

Abstract: Purpose The religious-based brands are increasing daily, and different organizations target religious consumers. However, a scarcity of research in developing nations makes it difficult to determine how customers evaluate religious brands. This study aims to develop a model based on Ajzen’s (1985) theory of planned behaviour (TPB). It incorporates the three mediating factors of religious brand attitude, subjective norms and perceived behavioural control. Design/methodology/approach A total of 499 (232 Malay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Several previous studies have also identified crucial aspects of Islamic branding among Muslims and determined which aspects of Islamic brands motivate consumers to purchase those products. Research findings reveal that the motivating factors for Muslims to buy Islamic brands are primarily based on the brand's origin, followed by customer-centric and compliance-oriented brands [47]. Then, a study found that product quality, Islamic physical attributes, and Islamic beliefs significantly influence brand image and consumer satisfaction.…”
Section: Previous Studymentioning
confidence: 96%
“…Several previous studies have also identified crucial aspects of Islamic branding among Muslims and determined which aspects of Islamic brands motivate consumers to purchase those products. Research findings reveal that the motivating factors for Muslims to buy Islamic brands are primarily based on the brand's origin, followed by customer-centric and compliance-oriented brands [47]. Then, a study found that product quality, Islamic physical attributes, and Islamic beliefs significantly influence brand image and consumer satisfaction.…”
Section: Previous Studymentioning
confidence: 96%